Resistance to proteasome inhibitors in cancer : molecular mechanisms and strategies to overcome resistance - Dou, Q. Ping (Resistance to Targeted Anti-Cancer Therapeutics, 2014)
The book explores cutting-edge strategies to overcome proteasome inhibitor resistance, including the second generation 20S proteasome inhibitors, novel combinational therapies, and new targets in the ubiquitin-proteasome pathway (e.g., ubiquitin E3 ligases, deubiquitinases, 19S proteasomal ATPases, histone deacetylases, oxidative stress and proteotoxic stress pathways and pharmacogenomic signature profiling) in resistant cancer cells. The mechanisms of action and resistance of proteasome inhibitors, such as bortezomib and carfilzomib in human cancers, including multiple myeloma, mantle cell lymphoma, acute leukemia, and solid tumors are explored in depth in this volume. This timely volume unveils the most current discoveries of the mechanisms behind proteasome inhibitor resistance, which will help illuminate the future of cancer therapies.